Upaya Pemberian Layanan Bimbingan Kelompok Teknik Fokus Grup Diskusi (FGD) dengan Pendekatan Nilai Karakter Religius pada Rehabilitasi Pecandu Narkoba di Yayasan Rumah Sehat Harapan Binjai - Robby Effendi; Widya Utami Lubis (Journal on Education, 2023)
The type of research used in this research is guidance and counseling action research using two cycles. The subjects of this study were 6 counselees at the Harapan Binjai Healthy Home Foundation. Where the 6 counselees are counselees who are being hospitalized. This study aims to provide focus group discussion (FGD) technical group guidance services with a religious character value approach in the rehabilitation of drug addicts at the Rumah Sehat Harapan Binjai Foundation. Data collection methods used are observation, interviews and documentation. The data analysis technique in this study was carried out on the results of observations, data analysis in this study was a qualitative description of counselees between the initial conditions (pre-cycle) and cycle I and cycle II (post-cycle). The results of the research are that the researcher conducted participant observation and conducted interviews with foundations and counselees, besides that it was supported by documentary data related to this research. Efforts to approach the value of religious character through the FGD technique group guidance services carried out in cycle I and Cycle II at the Rumah Sehat Harapan Binjai Foundation's Drug Rehabilitation Center to assist counselees in recovery have proven successful, as can be seen from the results of changes in religious character in counselees. Changes in religious character can be seen from the punctuality of the counselee taking water for ablution, carrying out congregational prayers, reading the Qur'an in his spare time, being tolerant of fellow friends, being responsible, caring for the environment, and caring for friends.